Synthesis and characterization of one dimensional modified cobalt Nanowires for nanoscale mechanical - Mahendran, Samykano; Md. Mustafizur, Rahman; Kumaran, Kadirgama; Jose, Rajan; Devarajan, Ramasamy; Muhamad, Mat Noor; Nurul Akmal, Che Lah; Pooria, Pasbakhsh (2016)
The present research and dissertation focuses on: 1. Experimental synthesis of electrodeposited Co nanowires at different current densities and external magnetic fields, 2. Physical properties characterization of the synthesized nanowires to understand their morphology, structural and crystallographic properties. Key research insights from the present experimental research include: Electrodeposition method consistently synthesizes high purity Co nanowires (98% and higher based on energy dispersive spectroscopy (EDS)) with a significant improvement in surface morphology when magnetic field is present during synthesis; X-ray diffraction (XRD) characterization and analysis indicate that electric current density has significant influence on the crystal orientation of Co nanowire, while a decrease in crystal size was noticed with increased magnetic field intensity for same current densities.